Effectiveness of the RADEC Learning Model in Natural and Social Sciences Learning to Improve Science Literacy of Fifth Grade Elementary School Students - Khafizah, Asha Quranul; Sopandi, Wahyu (International Conference on Elementary Education, 2025)
This study aims to investigate the effectiveness of the RADEC (Read, Answer, Discuss,Explain, Create) instructional model in enhancing science literacy among fifth-grade students in SocialScience and Natural Science (IPAS) lessons. The RADEC model was implemented to replaceconventional teacher-centered teaching methods, which limit student engagement in the learningprocess. A quantitative research approach with a quasi-experimental design was employed, involvingtwo groups: the experimental group utilizing the RADEC model and the control group employingtraditional teaching methods. Data were collected through a science literacy assessment consisting ofmultiple-choice and essay questions, which were subjected to validity and reliability tests. The resultsindicated that the experimental group demonstrated a significant improvement, with an average N-Gainof 8.21, whereas the control group showed minimal improvement with an N-Gain of 0.07. These findingssuggest that the RADEC model is more effective in fostering science literacy compared to conventionalteaching methods. However, factors such as lesson duration, student engagement, and teacherreadiness should be carefully considered to optimize the model’s implementation. The studyrecommends extending lesson durations, providing comprehensive teacher training for the RADECmodel, and enhancing student participation through the integration of technology and interactive media.